Análisis de las políticas públicas productivas generadas en el Ecuador, aplicadas en la zona de planificación 4 en el período 2010-2014 - Loor Cedeño, Evelin Lisseth (2014)
The present work was carried out in Ecuador in the area of planning 4, which comprises the province of Manabí and Santo Domingo de los Tsahalis, with reference to Manta, Portoviejo and Chone and Santo Domingo being the main objective a study of productive public policies generated in the Ecuador applied in the area of planning 4 in the 2004-2010 period to get to know its incidence in the production. The techniques used in the investigation were the collection of information, analysis of the application of productive public policy, reporting and socialization of the results found. With regard to the methodology applied the deductive method allowing to know each one of the causes of productive public policies, likewise descriptive research enabled base and determine the detailed descriptions of situations, events, performances, persons and behaviors, the instrument used was the study field in order to investigate the established process and thus comply with the analysis of the compiled resultthen was the interview with the leaders of the vestry, to know the assigned headings for each work or service of the parish budget its socio-economic impact.Executed the document review establishing records of productive public policies in the area of planning 4 and thus began with the collection of information relevant to the proposed study to determine the analysis, then report and socialize it with managers of MAGAP.